2016
DOI: 10.1002/ajmg.b.32478
|View full text |Cite
|
Sign up to set email alerts
|

Investigating shared aetiology between type 2 diabetes and major depressive disorder in a population based cohort

Abstract: Type II diabetes (T2D) and major depressive disorder (MDD) are often co‐morbid. The reasons for this co‐morbidity are unclear. Some studies have highlighted the importance of environmental factors and a causal relationship between T2D and MDD has also been postulated. In the present study we set out to investigate the shared aetiology between T2D and MDD using Mendelian randomization in a population based sample, Generation Scotland: the Scottish Family Health Study (N = 21,516). Eleven SNPs found to be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 23 publications
0
33
2
Order By: Relevance
“…Twin studies have previously shown genetic overlap between MDD and type 2 diabetes, but evidence from genetic studies has been weaker. The current study, however, does show evidence for a shared genetic aetiology between MDD and type 2 diabetes based on both polygenic risk scores and genetic correlations (21)(22)(23).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Twin studies have previously shown genetic overlap between MDD and type 2 diabetes, but evidence from genetic studies has been weaker. The current study, however, does show evidence for a shared genetic aetiology between MDD and type 2 diabetes based on both polygenic risk scores and genetic correlations (21)(22)(23).…”
Section: Discussioncontrasting
confidence: 83%
“…Studies using twin data also showed that the phenotypic association between MDD and type 2 diabetes was partly due to genetic effects (21). This finding has been replicated using a polygenic risk score approach(22), but not using genetic correlations (22,23). The Brainstorm Consortium did not find a significant genetic correlation between MDD and stroke(24), while Wassentheil-Smoller et al(25) showed that higher polygenic risk for MDD was associated with increased risk for stroke, in particular small vessel disease.…”
Section: However It Remains Unclear To What Extend These Mechanisms mentioning
confidence: 96%
“…No single type 2 diabetes risk SNP was associated with major depression in the MR analyses. In the same way, the results for the polygenic risk scores analyses and also the linkage disequilibrium score regression analyses showed no consistent evidence of genetic overlap between major depression and type 2 diabetes . However, the lack of genetic studies that explain the link between depression and diabetes does not reject the common ground hypothesis, as we know that the genetic predisposition of both diabetes and depression is modest.…”
Section: What We Now Know After 25 Years Of Research Into Diabetes Anmentioning
confidence: 90%
“…Based on the common ground hypothesis, several biological mechanisms have been associated with poor diabetes outcomes in people with diabetes and depression [31][32][33][34][35][36][37]. This hypothesis assumes that diabetes and depression have common denominators, including genetic factors, overactivation of the innate immune system or dysregulation of the HPA axis.…”
Section: Mechanisms Linking Depression and Diabetesmentioning
confidence: 99%
“…Furthermore, the study found no association between T2DM and depression at the phenotypic level (adjusted P≤0.65). Clarke et al [ 60 ] in 2017 used Mendelian randomization in a populationbased cohort of 21,516 individuals to test the association between MDD and 11 SNPs previously found to be associated with T2DM. In their analysis, only the A allele of rs6808574 was negatively associated with MDD.…”
Section: Proposed Mechanisms Underlying the Relationship Between Deprmentioning
confidence: 99%